THE USE OF SCALES IN THE KOTA FAJAR’S VILLAGE FISH MARKET ACEH SELATAN FROM THE PERSPECTIVE OF FIQH MUAMALAH - Nahara Eriyanti (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2022)
Market is one of the means used to carry out buying and selling transactions. Buying and selling that took place at the village of Kota Fajar fish market involved traders using scales that were not suitable for use, causing the fish to be weighed not according to their proper weight. Scales are important equipment that must be owned by traders who aim to find out the exact size of the fish being traded. Traders in the fish market generally use spring scales in buying and selling because they are very easy to use. This study aims to find out how the practice of buying and selling fish and the mechanism of traders in the fish market in using scales and how to use scales in the village of Kota Fajar fish market in the perspective of fiqh muamalah in terms of the tadlis elements’s existence. In this study, the authors used a descriptive analysis method with primary data obtained from field research and secondary data obtained from library research. The results of the study showed that the practice of buying and selling at the village of Kota Fajar fish market is that traders sell fish by using a spring scale as a weighing device, but there are also some traders selling fish by stacking it. The use of scales by fish traders is not fully follow fiqh muamalah and there is an element of tadlis in quantity which causes trading to be invalid, where fish traders still use spring scales which are rusty and the springs are weak which causes the measurements to be inaccurate, and there is the intentional element is carried out by the fish trader even though he knows that the scales used are not suitable for use, resulting in the buyer experiencing a loss.